1997
DOI: 10.1121/1.418178
|View full text |Cite
|
Sign up to set email alerts
|

Pitch and loudness estimation for single and multiple pulse per period electric pulse rates by cochlear implant patients

Abstract: Numerical estimates of loudness and pitch for electric pulse rates were obtained from 14 patients using the 22 electrode cochlear implant manufactured by Cochlear Limited. Six patients were postlinguistically deafened adults, and eight patients were adults and children who became deaf very early in life. Comparisons were made between two types of pulse rate patterns. The SPP pulse pattern presented a single pulse every period, the inverse of the pulse rate. The MPP pulse pattern presented multiple pulses in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Increasing the rate of stimulation from 100 pps up to about 600 pps produces increasingly higher pitch sensations, and this effect tends to asymptote at higher rates (Simmons et al 1979;Eddington 1980;Tong et al 1983;Townshend et al 1987;Busby and Clark 1997). In this study, stimulation rates were always higher than 700 pps and were held constant during the experiments.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Increasing the rate of stimulation from 100 pps up to about 600 pps produces increasingly higher pitch sensations, and this effect tends to asymptote at higher rates (Simmons et al 1979;Eddington 1980;Tong et al 1983;Townshend et al 1987;Busby and Clark 1997). In this study, stimulation rates were always higher than 700 pps and were held constant during the experiments.…”
Section: Discussionmentioning
confidence: 77%
“…Pitch sensations produced by multichannel cochlear implants have been extensively investigated in bilaterally deaf subjects using pitch-ranking experiments (Simmons et al 1979;Shannon 1983;Townshend et al 1987;Dorman et al 1990;Busby et al 1994;Nelson et al 1995;Collins et al 1997;Collins and Throckmorton, 2000) or pitch-estimation experiments (Eddington 1980;Tong et al 1983;Tong and Clark 1985;Shannon 1993;Busby et al 1994;Cohen et al 1996a;Busby and Clark 1997;Collins et al 1997). These studies demonstrated that electric stimulation of the ear produced complex auditory sensations, one component of which was similar to pitch.…”
Section: Introductionmentioning
confidence: 99%
“…For example, CIs have up to 22 electrodes, but clinical and psychophysical studies show that users do not receive functional benefit on all channels (Busby and Clark 1997;Chatterjee and Shannon 1998;Collins et al 1997;Shannon et al 2004). Additionally, tissue-electrode interactions cause fibrosis with deleterious effects (Bas et al 2012).…”
Section: Potential Applications and Future Directionsmentioning
confidence: 99%
“…However, challenges remain in the design of these and other neuroprosthetic devices, given the drawbacks of conventional electrical stimulation (Grill et al 2009). Tissue-electrode electrochemical interactions induce fibrosis with deleterious effects (Bas et al 2012), and electrical current spread can lead to interference among channels (Busby and Clark 1997;Chatterjee and Shannon 1998;Collins et al 1997). In CI patients, the loss of perceptual channels results in a poor performance for music perception and word recognition in noisy environments (Drennan and Rubinstein 2008;McDermott 2004;Spahr et al 2008).…”
mentioning
confidence: 99%
“…Some pitch information is conveyed to CI users via periodicity in the temporal envelope of the pulse trains or, in the case of low pulse rates (less than about 300 Hz), by the pulse rate itself (e.g., Busby and Clark 1997;Kong et al 2009). Carlyon and colleagues have shown that CI users are often sensitive to changes in pulse rates in ways that resemble the sensitivity shown by normal-hearing (NH) listeners when presented with acoustic pulse trains that are high-pass filtered to remove potentially resolved spectral components (e.g., Carlyon et al 2002Carlyon et al , 2008.…”
Section: Introductionmentioning
confidence: 99%